In-shoe plantar pressures and ground reaction forces during overweight adults' overground walking - Castro, Marcelo Peduzzi (2014)
Purpose: Because walking is highly recommended for prevention and treatment of obesity and some of its biomechanical aspects are not clearly understood for overweight people, we compared the absolute and normalized ground reaction forces (GRF), plantar pressures, and temporal parameters of normal-weight and overweight participants during overground walking. Method: A force plate and an in-shoe pressure system were used to record GRF, plantar pressures (foot divided in 10 regions), and temporal parameters of 17 overweight adults and 17 gender-matched normal-weight adults while walking. Results: With high effect sizes, the overweight participants showed higher absolute medial-lateral and vertical GRF and pressure peaks in the central rearfoot, lateral midfoot, and lateral and central forefoot. However, analyzing normalized (scaled to body weight) data, the overweight participants showed lower vertical and anterior-posterior GRF and lower pressure peaks in the medial rearfoot and hallux, but the lateral forefoot peaks continued to be greater compared with normal-weight participants. Time of occurrence of medial-lateral GRF and pressure peaks in the midfoot occurred later in overweight individuals. Conclusions: The overweight participants adapted their gait pattern to minimize the consequences of the higher vertical and propulsive GRF in their musculoskeletal system. However, they were not able to improve their balance as indicated by medial-lateral GRF. The overweight participants showed higher absolute pressure peaks in 4 out of 10 foot regions. Furthermore, the normalized data suggest that the lateral forefoot in overweight adults was loaded more than the proportion of their extra weight, while the hallux and medial rearfoot were seemingly protected.